Luminescent CaTiO3:Yb, Er nanofibers co-conjugated with Rose Bengal and gold nanorods for potential synergistic photodynamic/photothermal therapy. Issue 26 (12th June 2017) - Fu, Yike; Liu, Heng; Ren, Zhaohui; Li, Xiang; Huang, Jie; Best, Serena; Han, Gaorong
Abstract : CaTiO3 :Yb, Er nanofibers, co-conjugated with Rose Bengal and gold nanorods, enable a synergistic photodynamic/photothermal phenomenon for superior cancer cell killing effect. Abstract : Photodynamic therapy (PDT) and photothermal therapy (PTT) have been explored widely for application in cancer treatment. In this work, we describe the synthesis of CaTiO3 :Yb, Er (CTO) nanofibers co-conjugated with Rose Bengal (RB) and gold nanorods (AuNRs), which offer the potential for combined upconversion photoluminescence (UCPL) and enhanced, synergistic PDT and PTT. Based on this delivery platform, RB and AuNRs served as the PDT and PTT agents, respectively. RB and AuNRs have strong and well-matched absorption with the green and red emissions of UCPL CTO nanofibers respectively, hence a single 980 nm continuous wave laser with deep tissue penetration can be employed to allow PDT and PTT to occur simultaneously. The nanocomposite can effectively convert the near-infrared (NIR) radiation from the laser into a combination of targeted hyperthermia and generation of reactive oxygen species (ROS). In comparison with PDT or PTT alone, the combined PDT/PTT treatment showed significantly enhanced suppression of the viability of Hep G2 cells in vitro, demonstrating its potential for use in oncology.